A study on the development of jackfruit candy bar - Eala, Merlinda G. (1996.)
The study was conducted, to develop a jackfruit candy formulation.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Jackfruit; Candy bar